The Effects of Exercise, Motivation and Parent´s Education on Academic Achievement Among Adolescents in Iceland: A Cross-sectional Study - Jóhann Pétur Fleckenstein 1994- (2018)
Academic achievement is an important factor regarding every person´s life. Therefore, it is vital to examine factors concerning it. This study was conducted to examine the effects of exercise, parent´s education, student motivation and gender on academic achievement among adolescents in Iceland. The study used pre-existing data, collected by The Icelandic Research Centre for Social Research and Analysis (ISCRA) in 2016. Participants were 2008 adolescents from every secondary school in Iceland. Age ranged from 15-21 years old (Mage = 17.4). Gender distribution was rather equal, 49.1% were males and 50.9% were females. Results using hierarchical linear regression indicate that exercise, parent´s education and student motivation have positive effect on academic achievement among adolescents. Furthermore, females seem to show better academic achievement than males. The study concludes that many factors impact adolescent's academic achievement and adolescents need to be apprised of these factors and their positive effects. Keywords: Adolescents, exercise, parent´s education, motivation, gender difference, academic achievement Námsárangur er mikilvægur þáttur í lífi flestra. Því má færa rök fyrir mikilvægi þess að rannsaka þætti sem hafa áhrif á námsárangur. Núverandi rannsókn rannsakaði áhrif hreyfingar, menntunar foreldra, áhugahvatar til náms og kyns á námsárangur ungmenna á Íslandi. Rannsóknin notaði eldri gögn frá Rannsókn og greiningu (R&G) frá 2016. Þátttakendur voru 2008 ungmenni frá öllum framhaldsskólum á Íslandi. Aldur þátttakenda var á bilinu 15-21 árs (Maldur = 17,4). Kynjaskiptingin var fremur jöfn, 49,1% voru karlkyns og 50,9% voru kvenkyns. Niðurstöður út frá aðhvarfsgreiningar líkani gefa til kynna að hreyfing, menntun foreldra og áhugahvöt til náms hafi jákvæð áhrif á námsárangur ungmenna. Einnig virðist sem stelpur njóti betri námsárangurs en strákar. Rannsóknin sýnir að það eru margir þættir sem hafa áhrif á námsárangur ungmenna. Jafnframt sýnir hún fram á mikilvægi þess að ungmenni fái ...